Lafadz Gharib Dalam Q.S. Al-Nur, Al-Furqon, Al-Syu'ara', Al-Naml, Al-Qashash, Dan Al-Ankabut Analisis Berdasarkan Tafsir Al-Misbah dan Al-Qurthubi - Yuwanda Issadora; Nayla Batasya Aisya R (FIRDAUS, 2025)
This research examines the gharib lafadz (foreign vocabulary) contained in Q.S. Al-Nur, Al-Furqon, Al-Syu'ara', Al-Naml, Al-Qashash, and Al-Ankabut are based on the book 'Umdat al-Mufid fi Gharib al-Qur'an by Abu Muhammad Makki ibn Abi Talib al-Qaisi, and interpreted through Tafsir Al-Misbah and Tafsir Al-Qurthubi. This study aims to: (1) describe the general description of the six surahs; (2) classifying the gharib lafadz contained in it; and (3) analyzing the interpretation of these lafadz. The method used is descriptive qualitative with a linguistic interpretation approach. The research results show that Q.S. Al-Nur contains 28 gharib lafadz, Al-Furqon 15 lafadz, Al-Syu'ara' 21 lafadz, Al-Naml 17 lafadz, Al-Qashash 31 lafadz, and Al-Ankabut 6 lafadz. Each lafadz has a specific and contextual meaning so that it contributes significantly to the depth of the meaning of the verse. This study confirms that understanding the lafadz gharib is the main key in interpreting the Qur'an accurately.